14. Pablo De Sarasate - Andalusian Romance for Violin and Piano - Ioniţă Raluca Dobre (Sciendo, 2023)
Pablo de Sarasate was a famous violinist and composer of Spanish origin. In his creations, Sarasate highlighted to the maximum the technical and interpretative potential of the violin, composing both works for violin and orchestra (including fantasias on operatic themes) and musical miniatures for violin and piano. Sarasate's musical language is mainly inspired by Spanish folklore.